Periodontal and dental effects of surgically assisted rapid maxillary expansion, assessed by using digital study models - Danilo Furquim Siqueira; Mauricio de Almeida Cardoso; Leopoldino Capelozza Filho; Dov Charles Goldenberg; Mariana dos Santos Fernandes (Dental Press Editora, 2015)
OBJECTIVE: The present study assessed the maxillary dental arch changes produced by surgically assisted rapid maxillary expansion (SARME). METHODS: Dental casts from 18 patients (mean age of 23.3 years) were obtained at treatment onset (T1), three months after SARME (T2) and 6 months after expansion (T3). The casts were scanned in a 3D scanner (D-250, 3Shape, Copenhagen, Denmark). Maxillary dental arch width, dental crown tipping and height were measured and assessed by ANOVA and Tukey's test. RESULTS: Increased transversal widths from T1 and T2 and the maintenance of these values from T2 and T3 were observed. Buccal teeth tipping also showed statistically significant differences, with an increase in all teeth from T1 to T2 and a decrease from T2 to T3. No statistically significant difference was found for dental crown height, except for left first and second molars, although clinically irrelevant. CONCLUSION: SARME proved to be an effective and stable procedure, with minimum periodontal hazards.